Pelaporan Corporate Social Responsibility Perbankan Syariah dalam Rangka Meningkatkan Nilai Perusahaan yang Terdaftar di Otoritas Jasa Keuangan - Puja Rizqy Ramadhan; Fitri Yani Panggabean; Nia Pratiwi Lubis (Forum Kerjasama Pendidikan Tinggi, 2022)
The purpose of this study is to find out that Islamic banking registered with the Financial Services Authority (OJK) reports on corporate social responsibility (CSR) or not, the suitability of CSR reporting carried out by Islamic banking based on sharia enterprise theory, and the effect of CSR reporting in increasing the value of CSR. company. This research was conducted at Islamic commercial banks registered with the OJK. Determination of the research sample using purposive sampling technique. The type of data used is secondary data. Data collection is done by using documentation study techniques. This type of research is quantitative research using descriptive-quantitative analysis techniques and simple linear regression analysis. The results of this study indicate that Islamic banking registered with the OJK has carried out CSR reporting, the suitability of CSR reporting carried out by Islamic banking is not 100% in accordance with sharia enterprise theory, and CSR reporting has no significant effect on firm value